2011
DOI: 10.1038/eye.2011.282
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold diode laser micropulse photocoagulation versus intravitreal injections of bevacizumab in the treatment of central serous chorioretinopathy

Abstract: Purpose To evaluate the treatment of central serous chorioretinopathy (CSC) with either subthreshold diode laser MicroPulse (SDM) or intravitreal bevacizumab (BCZ). Methods This comparative, controlled, prospective study conducted over a period of 10 months examined 52 eyes of 52 patients with (a) treatment with SDM at the active leakage site guided by fluorescein angiography (FA) (n ¼ 16 eyes), (b) intravitreal injection of 1.25 mg BCZ (n ¼ 10 eyes), or (c) observation (n ¼ 26 eyes). Outcome measures included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 29 publications
(40 reference statements)
3
75
2
1
Order By: Relevance
“…In contrast to our study, previous studies reported a treatment response after SML in up to 100% of patients and complete resolution of SRF in 33-75%, 18,19,[24][25][26] and for PDT a partial resolution of SRF in up to 100% and complete resolution of SRF in 81-100% after PDT. [13][14][15]27,28 This less favorable outcome in our cohort is potentially attributed to the severity of the disease in our patients with often long-standing disease accompanied by chronic retinal and choroidal changes.…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast to our study, previous studies reported a treatment response after SML in up to 100% of patients and complete resolution of SRF in 33-75%, 18,19,[24][25][26] and for PDT a partial resolution of SRF in up to 100% and complete resolution of SRF in 81-100% after PDT. [13][14][15]27,28 This less favorable outcome in our cohort is potentially attributed to the severity of the disease in our patients with often long-standing disease accompanied by chronic retinal and choroidal changes.…”
Section: Discussioncontrasting
confidence: 51%
“…Foveal thinning occurred more frequently in PDT group than in IVB group in both studies. Subthreshold laser photocoagulation (810 nm infrared diode) resulted superior to the IVB for resolution of SRF and BCVA improvement at 6 and 10 months after treatment in the study by Koss et al 33 Although our study confirmed the lack of efficacy of IVB for CSC over a 6-month period, the outcome of this treatment is still unknown. Despite the considerable available literature providing the possible efficacy of IVB for CSC, the majority of studies was simple interventional case series, and was not randomized.…”
Section: Discussionsupporting
confidence: 31%
“…Most case series reported no specific complications, although there is always some risk of postinjection endophthalmitis. 49 Most studies reported that IVB might be effective in terms of improving visual acuity and reducing CMT without significant complications and can be considered an optional intervention, 1,2,23,24,28,32,33 but these conclusions should be interpreted cautiously owing to the self-limiting nature of acute and even in chronic CSC. Moreover, it should be noted that the aqueous humor and plasma levels of VEGF were not significantly increased in patients with CSC compared with the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease in acute phase, is characterized by neurosensory detachment with subretinal fluid that spontaneously resolved with no treatment. But if it becomes chronic (CSCR), it can result in permanent vision loss with extensive RPE atrophy [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%